2017
DOI: 10.1253/circj.cj-17-0063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prognostic Values of Daytime and Night-Time Systolic Blood Pressures on Renal Outcomes in Patients With Chronic Kidney Disease

Abstract: Background: Differences in the predictive value of daytime systolic blood pressure (SBP) and night-time SBP by ambulatory blood pressure monitoring on renal outcomes have not been fully investigated in chronic kidney disease (CKD) patients. This study compared the prognostic value between daytime and night-time SBP on renal outcomes in CKD. Methods and Results:This prospective observational study included 421 patients. The composite renal endpoint was endstage renal disease (ESRD) or death. Cox models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Moreover, mean nocturnal SBP remained independently associated with plasma BNP in the model. This is consistent with previous studies showing the importance of nocturnal BP in predicting the progression of atherosclerosis, target organ damage, and cardiovascular outcome, [16][17][18][19][21][22][23] and may support the clinical utility of nocturnal BP assessment for better managing patients with severe AS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, mean nocturnal SBP remained independently associated with plasma BNP in the model. This is consistent with previous studies showing the importance of nocturnal BP in predicting the progression of atherosclerosis, target organ damage, and cardiovascular outcome, [16][17][18][19][21][22][23] and may support the clinical utility of nocturnal BP assessment for better managing patients with severe AS.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that target organ damage and prognosis are more closely associated with nocturnal BP than with diurnal BP or clinical measurement. [17][18][19][20][21][22] Moreover, nocturnal BP monitoring provides data on variability, which has been proven to be associated with subsequent cardiovascular events and cardiovascular mortality. 16,23,24 To date, however, the association between nocturnal BP variables and BNP A ortic stenosis (AS) is common with aging and its prevalence is gradually increasing worldwide.…”
mentioning
confidence: 99%
“…Death occurred before reaching ESRD. Information regarding patient death and definitions of censored patients are described in our previous report [13]. In total, 69 patients were censored; 63 were lost to follow-up and 6 required maintenance hemodialysis because of acute exacerbation of kidney function due to infectious diseases or congestive heart failure.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical assessments at admission and the definitions of hypertension, diabetes mellitus, smoking, and dyslipidemia are described in our previous report [13]. An echocardiogram was performed to assess left atrial diameter and left ventricular ejection fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Controversy remains regarding the appropriate time of BP measurement in relation to renal outcomes or death. In the present study, daytime BP was of greater importance in predicting ESRD, whereas nighttime BP was of greater importance [19,20]. In a study on 682 hypertensive patients who underwent echocardiography, nocturnal BP, rather than non-dipping, showed better prediction of left ventricular hypertrophy (LVH), especially in patients with a high cardiovascular risk [21].…”
Section: Discussionmentioning
confidence: 48%